Comparative analysis of post- Second World War urban environments in Westerns and Central Europe and Southeast Asia - Kozlowski, Marek (Peter Lang Publication, 2019)
The physical destruction of the urban environment during a war can occur as a result of damage through air and missile raids, a nuclear explosion, devastation through civil uprisings, attacks on the urban infrastructure and, more recently terrorist attacks. There are also non-physical damages; such as biological warfare and cyber-attacks that can cause significant chaos within an urban conurbation. This study focuses on the consequences of the Second World War in the urban environments of cities in Western and Central Europe and Southeast Asia, and illustrates the different approaches and paths individual nations have followed in rebuilding their damaged urban fabric. The Second World War resulted in the considerable destruction of the urban fabric throughout Western and Central Europe. Many German cities were partially or almost destroyed as a result of air bombing. Other cities in Central Europe became living battlefields, and suffered significant devastation because of air raids and the passing front. After the Second World War, state and local authorities in Europe placed a strong emphasis on rebuilding the cities, and as a result, urban planning became one of the leading professions. In Southeast Asia, the situation was different as the urban population percentage was significantly lower than in Europe, and therefore the majority of the fighting and war activities took place in the rural areas. Consequently, the destruction of urban areas had a lesser impact on the local economies, and rebuilding cities was not a decisive post-war economic driver as in the case of...